Effect of Adaptive Exercise on Body Temperature in Children with Motoric Disorder - Mulyadi, Soffil Yudha; Rejeki, Purwo Sri; Tinduh, Darmayanti; Sari, Gadis Meinar; Prasetya, Rizka Eka (Folia Medica Indonesiana, 2020)
Motoric disorder in child increased every year, especially cerebral palsy. Children with motoric disorder which is majority experiencing long immobilization results in their general condition declining. One of this declining appears on body temperature in child, even lead to hypothermia. A simple exercise which applicatively performed at home can be a simple solution to maintain general condition, especially body temperature. The purpose of this study was to determine effect of adaptive exercise on body temperature change in children with motoric disorder. This study was an experimental study of one group pre and posttest. A total of 31 children (11 girls and 20 boys) aged 2-10 years old performed adaptive exercise consist of warming up 5 minutes, core movement 25 minutes, cooling down 5 minutes. Data were analyzed by paired T test. Body temperature in pretest was 36.12 ± 0.53oC, and body temperature in posttest was 36.63 ± 0.6oC, with p = 0.00. Adaptive exercise can increase body temperature but still in normal range.